Symbiosis of greenery with built form. A holistic, systems, multi-level approach - Francesca Scalisi; David Ness (Agathón, 2022)
Climate change is an effect of human action. It affects the balance of the planet mainly because of the ongoing growth of cities and increased consumption, which leads to the indiscriminate use of non-renewable resources. One solution for this problem is often the use of ‘nature-based solutions’. They can offer many advantages and services for humans and the ecosystem, as long as greenery – ecological per se – is not commoditised, effectively reducing biodiversity and increasing pollution levels. This paper questions the ‘unlimited’ growth model and some uses of greenery in the built form in favour of an approach based on ‘sufficiency’. Holistic and illuminating good practices and experiments in biophilic design, supported by frontier technologies, based on vernacular practices and in collaboration with local communities, are capable of looking at the big picture and tackling the climate challenge in a wider context and at different scales.